Trade Flow of Nepal: A Gravity Model Approach - Kadel, Suren Babu (Management Dynamics, 2023)
The gravity model of panel data analysis is applied in the study to examine the relationship between Nepal’s trade volume and economic growth using data from the period 2001 to 2020. The GDP of both Nepal and its trading partners are proven to have a favorable impact on Nepal’s trade volume. Trade is preferred to be conducted with the nation having a higher GDP. The population of Nepal has a significant and positive impact on trade. It suggests that encouraging the country’s working-age people to find employment will help to advance trade. However, the distance between Nepal and trading partner country of Nepal has negative and significant impact over the trade of Nepal.